THE CONCEPT OF FLOW AS MEDIATING VARIABLES ON THE RELATIONSHIPS BETWEEN PERCEIVED USEFULNESS WITH REPURCHASE INTENTION - Nurcholis, Lutfi; Miftaqulkismay, Sita (Jurnal Aplikasi Manajemen, 2021)
In the existing literature, studies rarely found in the context of mobile shopping incorporate the concept of flow in their research. This study aims to examine and analyze the role of the concept of flow in which three dimensions of flow are chosen, including flowconcentration, flow-control, and flow-enjoyment as an intervening variable to perceived usefulness and purchase intention through Shopee shopping services. The concept of flow related to studies with the context of mobile shopping is scarce. The type of this study is explanatory research. For this reason, this study had been examined 153 respondents who have used Shopee shopping services. Data were collected using a questionnaire and analyze for in-depth studies of related variables. The results show that the concept of flow from the three dimensions is proven to be an intervening variable between perceived usefulness and repurchase intention. Future exploration additionally can be applied to the business division with a bigger scope and more extensive topographical region.